THE EFFECT OF QUALITY OF SERVICE AND PRICE ON CUSTOMER SATISFACTION ON GRILLED CHICKEN RESTAURANTS OF PAK ATOK BAKOM CIAWI BOGOR - Tanti Setiowati; Sakti Brata Ismaya (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2022)
The purpose of this study was to determine the effect of service quality and price on customer satisfaction on grilled chicken restaurants of Pak Atok Bakom, Ciawi Bogor. This study is a quantitative approach. The population in this study are consumers who visit the Grilled Chicken Restaurants of Pak Atok Bakom, Ciawi Bogor. Meanwhile, the sample used was based on the Accidental method, which is a technique for determining the sample based on needs only, members who were met by researchers and were willing to become respondents. The type of data used in this study is quantitative data which obtained through an online questionnaire, namely the Google Form. Questionnaires are used to obtain respondent data regarding service quality, price and customer satisfaction with data sources obtained directly from consumers or customers who have been or are now customers of Pak Atok Bakom's Grilled Chicken Restaurant in Ciawi Bogor. Moreover, the data analysis carried out by several test, namely Validity test, Reliability test, and Hypothesis test. The finding reveals that service quality has a significant effect on customer satisfaction and the price has a significant influence on customer satisfaction. Likewise, service quality and price has a significant effect on customer satisfaction, it is proven by path coefficient value of service quality and price on customer satisfaction which are 0,000 and the t-statistic is 5,381, hence the t-statistic is significant because > 1,96 with p value < 0,00.